Applying Evaluative Inquiry: Experience and Recommendations from the Field. Issue 7 (22nd August 2020) - Paydon, Marie E.; Ensminger, David C.; De Kluyver, Marlies
Abstract: Evaluative Inquiry (EI) is a process for how evaluation and social interactions provide a structured model which promotes individual, team, and organizational learning. We share experiences and guidance from the field which highlight benefits, challenges, and lessons learned. These include guiding principles for promoting, planning, implementing, and maintaining EI. Finally, we share additional items to consider that are not part of the formal EI model that we found important through our experience.